Strengthening Discipline Culture Through Digital Innovation: Managerial Readiness and PDCA Implementation - Wahyu Pawaka; Sobari Sobari (Journal of Innovation and Research in Primary Education, 2026)
Discipline constitutes a fundamental pillar of vocational education, yet many schools continue relying on manual or semi-digital recording methods that lack real-time monitoring and integration capabilities. This qualitative case study examined managerial readiness for implementing digital discipline information systems through the PDCA (Plan-Do-Check-Act) framework at two Indonesian vocational schools utilizing Skul.id application. Data were collected through in-depth interviews with multiple stakeholders, participatory observations, and document analysis, then analyzed using thematic analysis guided by PDCA phases. Implementation successfully enhanced student attendance regularity, reduced tardiness from 15% to 6%, and strengthened parental involvement through real-time notifications. However, challenges emerged including infrastructure limitations, internet connectivity issues, and incomplete system integration with violation recording. Unexpected positive outcomes included spontaneous peer support networks and behavioral improvements extending beyond attendance compliance. Findings reveal that successful digital discipline system implementation depends critically on organizational readiness dimensions including infrastructure capacity, comprehensive stakeholder socialization, and continuous improvement mechanisms. The study contributes theoretically by integrating organizational change theory, technology readiness frameworks, and quality management principles to explain how managerial dimensions determine technology adoption success beyond technical functionality alone, addressing a significant knowledge gap in educational technology literature.